EKSTRAK ETANOL DAUN SUJI (Pleomele angustifolia) TERENKAPSULASI NANOPARTIKEL KITOSAN DALAM SEDIAAN KRIM TABIR SURYA DENGAN VARIASI TWEEN 80-SETIL ALKOHOL - Muhammad Ridho Putra Santosa; Malinda Prihantini (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
Antioxidants in the ethanolic extract of suji leaves (Pleomele angustifolia) have the potential as a sunscreen. The use of chitosan in the nanoparticle system is able to protect the degradation of flavonoids due to the influence of temperature and light. Tween 80 and cetyl alcohol play a strategic role in the formation of cream preparations. The purpose of this study was to determine the characteristics of sunscreen cream with variations of Tween 80-cetyl alcohol containing the active ingredient of ethanol extract of suji leaves encapsulated in a nanoparticle system. Chitosan nanoparticles of suji leaf ethanol extract (KEEDS) were prepared using ultrasonic agitation. KEEDS nanoparticles were made into cream preparations with variations of Tween 80-cetyl alcohol (T80:SA) FI (3:3)%, FII (3:10)%, FIII (10:10)%. The formed cream was observed for organoleptic, homogeneity, type of cream, and measured the value of pH, spreadability, adhesion, viscosity, and sunscreen activity using a UV-Vis Spectrophotometer at a wavelength of 290–320 nm. Organoleptic data, homogeneity, pH and cream type were analyzed descriptively, while the spreadability, adhesion, viscosity and sunscreen activity were analyzed using ANOVA with 95% confidence limit. KEEDS nanoparticle cream visually looks homogeneous, with a brownish white color, soft texture, and the aroma of suji leaves. The pH value of the preparation is 4.74-4.88, the type of cream is O/W. The variation of the T80:SA combination resulted in significant differences in the values of dispersion, adhesion, viscosity and sunscreen activity between the three formulas (sig < 0.05).